1-[3-Methyl-3-(2,4,6-trimethylphenyl)cyclobutyl]2-(thiomorpholin-4-yl) ethanone - Saracoglu, H; Soylu, S; Caliskan, N; Cukurovali, A; Yilmaz, I; Kazaz, C (Int Union Crystallography, 2005)
The title compound, C20H29NOS, the thiomorpholine ring adopts a chair conformation. The crystal structure is stabilized by intermolecular C - H . . . pi interactions.